IMPROVEMENT OF SUSTAINABLE DEVELOPMENT OF LARGE CITIES - and and (Municipal economy of cities. Series: «Economy science», 2013)
The application of strategic planning in the modern practice of sustainable development management of large cities. Analyzes the development of Kharkov, identify priority strategic directions for its future development. Proposed the establishment of a regional park "Science City - Kharkiv".